The Effect of Ladder Drills on the Shooting Skills of Futsal Players at SMKN 4 in Bengkulu City - Hafit Nopriansyah; Dody Ertanto; Desrio Windoro (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to examine the effect of ladder drill training on the shooting skills of futsal players at SMK Negeri 4 of Bengkulu City. The study was motivated by the relatively low shooting ability of the players, as reflected in inadequate shooting accuracy, insufficient kicking power, and poor movement coordination during shooting. This research employed an experimental method using a one-group pretest–posttest design. The study population consisted of students participating in the futsal extracurricular program at SMK Negeri 4 of Bengkulu City. A total of 20 students were selected as the sample using the total sampling technique. The research instrument was a futsal shooting skills test. The treatment consisted of ladder drill training conducted over 16 sessions within one month, with a training frequency of four sessions per week. Data were analyzed using the normality test and hypothesis testing through a t-test. The results revealed a significant improvement in the participants' shooting skills following the ladder drill training. The mean pretest score increased from 17.4 to 27.9 on the posttest. The t-test yielded a calculated t-value of 13.58, which exceeded the critical t-value of 1.729, indicating a statistically significant effect of ladder drill training on shooting skills. Furthermore, the percentage improvement in shooting performance was 60.34%. Based on these findings, it can be concluded that ladder drill training is effective in enhancing the shooting skills of futsal players at SMK Negeri of Bengkulu City